Analisis Perubahan Makna Gairaigo Dalam Website Marisol - Mohammad Septio Elkhaima; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
Gairaigo is a type of Japanese vocabulary that comes from a foreign language and then adapted to the Japanese linguistic rules. Along with its development, many gairaigo underwent language changes of meaning compared to its original meaning. This will make Japanese language learners confused because it can lead them to different perception and will result in misinterpretation about the gairaigo meaning. This study aims to describe the semantic change of gairaigo which derived from English on the Marisol website. The type of research is a qualitative research with descriptive method. The data collection technique used in this research is to use watch method and note-taking technique. The data analysis techniques used in this study are match method and determining element sorting technique. The data used in this study is gairaigo which has changed the meaning contained in the Marisol website. The data source is the Marisol website. The result of this study showed that there were 39 data that have semantic change (underwent changes of meaning), there are 14 data whose meanings change broadly, 24 data meanings change to narrow and 1 data have total change in meaning.